2017
DOI: 10.1021/acs.jctc.6b01059
|View full text |Cite
|
Sign up to set email alerts
|

Reparametrization of Protein Force Field Nonbonded Interactions Guided by Osmotic Coefficient Measurements from Molecular Dynamics Simulations

Abstract: There is a small, but growing, body of literature describing the use of osmotic coefficient measurements to validate and reparameterize simulation force fields. Here we have investigated the ability of five very commonly used force field and water model combinations to reproduce the osmotic coefficients of seven neutral amino acids and five small molecules. The force fields tested include AMBER ff99SB-ILDN, CHARMM36, GROMOS54a7, and OPLS-AA, with the first of these tested in conjunction with the TIP3P and TIP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 93 publications
2
79
0
Order By: Relevance
“…As noted earlier, Yoo & Aksimentiev have shown that increasing the σ value for the amino-carboxyl interaction fully corrects the osmotic behavior of glycine with both the AMBERff99SB-ILDN-phi and CHARMM36 force fields, 25 and we have recently shown that the same modification also improves the behavior of other amino acids. 27 In addition, we have shown that much-improved results for the same amino acids can be obtained with the GROMOS54a7 and OPLS-AA force fields by increasing or decreasing (respectively) the σ value for the same interaction. 27 …”
mentioning
confidence: 86%
See 2 more Smart Citations
“…As noted earlier, Yoo & Aksimentiev have shown that increasing the σ value for the amino-carboxyl interaction fully corrects the osmotic behavior of glycine with both the AMBERff99SB-ILDN-phi and CHARMM36 force fields, 25 and we have recently shown that the same modification also improves the behavior of other amino acids. 27 In addition, we have shown that much-improved results for the same amino acids can be obtained with the GROMOS54a7 and OPLS-AA force fields by increasing or decreasing (respectively) the σ value for the same interaction. 27 …”
mentioning
confidence: 86%
“…27 In addition, we have shown that much-improved results for the same amino acids can be obtained with the GROMOS54a7 and OPLS-AA force fields by increasing or decreasing (respectively) the σ value for the same interaction. 27 …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…only the thermodynamic properties used typically in the original parametrizations [101]. By considering both solubility and binding affinity on equal footing a thermodynamical consistent description of complex host-guest systems in complex solvent environments will become possible in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For this thesis, over 200 simulations were performed on systems that contained approximately 10000 atoms, were simulated for at least 100 nanoseconds, and represented interactions using the state-of-the-art, fixed-charge force fields described above. [12][13] Today, biological macromolecules are regularly simulated in attempts to address these two key issues: accurately representing these macromolecules on biologically meaningful timescales and sizes. A 2014 simulation study by Petrov and Zagrovic put simulation scale and force field accuracy to the test.…”
Section: Introductionmentioning
confidence: 99%